Transformation of SMEs: Strengthening Entrepreneurship and Product Innovation as Key Drivers of Business Evolution - Herman, Bahtiar; Bashir, Shahid; Syahnur, Khaerunnisa Nur Fatimah; Haslindah, Haslindah; Absah, Yeni (Hasanuddin Economics and Business Review, 2024)
The important role of Small and Medium Enterprises (SMEs) in driving economic growth requires a deep understanding of the factors that influence their performance. The number of samples in this study was 175 respondents, processed using the Structural Equation Modeling (SEM) method through the AMOS (Analysis of Moment Structure) program. This research explores the dynamics of entrepreneurial competence and product innovation as the main determinants of SME success. In the context of SMEs that have survived for two years in Gowa Regency, South Sulawesi, this research reveals that increasing entrepreneurial competence has a positive impact on business performance. Simultaneously, effective product innovation is proven to make a significant contribution to superior business outcomes. This study also highlights the mediating role of the market environment, demonstrating its influence on the relationship between entrepreneurial competence, product innovation, and business performance. These findings provide valuable insights for policy makers, educators and business actors who aim to increase the competitiveness and adaptability of SMEs amidst rapid business change.